2010
DOI: 10.1089/pho.2009.2647
|View full text |Cite
|
Sign up to set email alerts
|

Theoretic, Experimental, Clinical Bases of the Water Oscillator Hypothesis in Near-Infrared Photobiomodulation

Abstract: The objective of this review is to propose and document a role for the water oscillator in near-infrared (NIR) photobiomodulation. Greater understanding of the role of the water oscillator may add to a more-coherent description of central effects of NIR light on redox centers and key transmembrane enzymes such as cytochrome c oxidase (CcO). In addition, water provides a complementary pathway for absorption and transportation of NIR energy in photobiomodulation. Because of its unexpected potential, we propose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 125 publications
4
35
0
Order By: Relevance
“…The possibility of water acting as a chromophore in PBM studies has previously been discussed by Santana-Blank [36, 37] and Sommer [38, 39] (among others). Further studies will be necessary to confirm or refute this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of water acting as a chromophore in PBM studies has previously been discussed by Santana-Blank [36, 37] and Sommer [38, 39] (among others). Further studies will be necessary to confirm or refute this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…39 The chromophore in these situations is almost certainly water, possible present in biological membranes in some nanostructured form, that is different from bulk water allowing biological effects without gross heating of the tissue. 94,95 It is at present not clear at which wavelength CCO absorption ceases and water absorption commences to be important.…”
Section: Light Sources and Dosimetrymentioning
confidence: 99%
“…In another study, laser irradiation of mitochondria increased cytochrome c oxidase activity, polarographically measured levels of oxygen uptake, and subsequent ATP production [56]. Many other in vitro and in vivo studies of laser-induced cell growth have reported changes in cytochrome c oxidase activity and ATP production following irradiation [57][58][59][60][61][62][63][64][65].…”
Section: Cytochrome C Oxidasementioning
confidence: 99%